Antifungal effects and potential mechanisms of lonidamine in combination with fluconazole against Candida albicans. Issue 1 (2nd January 2021) - Chen, Xueqi; Shi, Yinping; Li, Yiman; Su, Shan; Wang, Peng; Sun, Shujuan
ABSTRACT: Objectives: The resistance of Candida albicans ( C. albicans ) to classical antifungals has been increasing significantly and poses great challenges to clinical treatment. The objective of this research is to evaluate whether the combination of lonidamine (LND) and fluconazole (FLC) have synergistic antifungal activity against C. albicans and to explore the underlying synergistic mechanisms against FLC-resistant C. albicans . Methods: The antifungal effect on resistant planktonic C. albicans and preformed biofilms were performed by broth microdilution assay and XTT reduction assay. The influence on hyphal growth, cellular ROS level, metacaspase activity and drug transporters were investigated by morphogenesis observation, DCFH-DA, FITC-VAD-FMK and rhodamine6G assay, respectively. Results: LND in combination with FLC exhibited synergistic antifungal effects against resistant planktonic C. albicans and preformed biofilms of C. albicans in the early stages (performed at 4 h and 8 h). The synergistic mechanisms associated with the inhibition of the hyphal growth and the activation of metacaspase, but were not related to mediate cellular ROS level or drug uptake and efflux in resistant C. albicans . Conclusion: LND combined with FLC exhibited synergistic antifungal activity against resistant C. albicans, and the synergistic mechanisms were related to anti-biofilms and reduce virulence factors. Expert opinion: The emergence of fluconazole-resistant Candida albicans strains poses great challenges to clinical treatment. Drug combination of non-antifungals and fluconazole has attracted a lot of attention to overcome Candida albicans drug resistance.